Stylo Store / Mohd Fazli Mohamed Mansha ... [et al.] - Mohamed mansha, Mohd Fazli; Timothy, Brayon Leo; Maidin, Mohd Faizal Fandi; Juim, Ferdolin; Abdullah, Md. Kamal Alham; Dani, Danel (2015)
Our company has been established in early 2015 to provide the end user for using our clothes and our latest design which is DENIM's clothes. Our target is aimed for those who still doing their studies and for those who not enough income. Our company name is STYLO Store, which the name itself related to our main purpose, to provide a stylish clothes for teenager that metrosexual. Our company is based on partnership concept, where all the members are also can be known as the founder. We believe that our clothes design purposes is the most significant equipment to boost their confident level in term of style.This is one of the examples how Malaysia can move forward through effort and the innovation of clothes.